2004
DOI: 10.1136/hrt.2003.014746
|View full text |Cite
|
Sign up to set email alerts
|

Mortality caused by acute myocardial infarction in Qatari women

Abstract: T he long held belief that coronary heart disease (CHD) in women has a more benign prognosis than in men has resulted in less aggressive diagnosis and management patterns. Contrary to this belief, CHD is the leading cause of death in white women aged 60 years or older in the USA and outnumbers the next 16 causes of death in women combined, including cancers. Furthermore, since 1980, death from CHD has declined dramatically in men in the western world but has increased in women. 1With the recent recognition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
3
9
0
Order By: Relevance
“…From a study by El-Menyar et al, [7] of 8,169 patients with acute coronary syndromes in six Middle Eastern countries, it was reported that women were more likely to have hypertension and diabetes. Women also had increases in hospital mortality and poorer treatment outcomes for acute coronary syndrome [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a study by El-Menyar et al, [7] of 8,169 patients with acute coronary syndromes in six Middle Eastern countries, it was reported that women were more likely to have hypertension and diabetes. Women also had increases in hospital mortality and poorer treatment outcomes for acute coronary syndrome [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Al Suwaidi and his colleages [20] revealed that in six Middle Eastern countries, water-pipe smokers tended to be female, and they had higher in-hospital complication rates including death, recurrent myocardial ischemia, heart failure, and cardiogenic shock than did the cigarette smokers. Consequently, the development of culturally appropriate and effective health promotion and CVD prevention programs that promote physical activities, healthy diet and non smoking among the Qatari female population is urgent [8,20]. Thus, the aim of this qualitative study was to explore how contextual factors such as social, cultural and economic factors influence Qatari women's participation in physical activities, dietary practices and smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, data from the Global Use of Streptokinase and Tissue Plasminogen Activator for Occluded Coronary Arteries (GUSTO-1) and International Study of Infarct Survival (ISIS-3) trials found that female gender appeared to be an independent predictor of mortality after AMI 1718 It should be noted that women are more likely to have ACS but without obstructive coronary artery disease due to endothelial dysfunction, microvascular disease or coronary artery spasm than men 23…”
Section: Discussionmentioning
confidence: 99%
“…The data were coded and entered into a computer using the Statistical Packages for Social Sciences (SPSS) [6,7]. Data are expressed as meanFstandard deviation (SD) unless otherwise stated.…”
Section: Statistical Methods and Analysismentioning
confidence: 99%
“…Epidemiological transition has already occurred in this community; a sharp decline in infectious and nutritional deficiency diseases and a gradual increase in chronic diseases have occurred in this country. In the last decade of the 20th century, cardiovascular diseases are the leading causes of morbidity and mortality in Qatar and this trend is increasing [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%